Adaptive and automatic Closed-Loop coordinated voltage control based model for optimal voltage control: A Case Study - Abdullah S.K.S.; Sarmin M.K.N.M.; Saadun N.; Azmi M.T.; Abidin I.Z.; Musirin I. (Praise Worthy Prize S.r.l, 2023)
Effective and efficient management of voltage control devices and reactive power resources is one of the most challenging tasks in power system operation. The need for proper voltage control is mainly to fulfill the following requirements: system security, economic operation and voltage quality. In Malaysian Transmission System (MTS), most of the voltage control devices and reactive power resources are manually control. Since the guidelines for controlling the primary and secondary voltage control are broad in nature, control actions could vary from one operator to another depending on experience, system information and knowledge. Tenaga Nasional Berhad (TNB) as system operator for MTS System believes that improvement in the approach and methods for voltage controls are desirable. This paper presents the newly developed hierarchical voltage control system called Adaptive and Automatic Closed-Loop Coordinated Voltage Control (A2 CLCVC) based system model as a possible solution for better voltage control within Malaysia Transmission System. The A2 CLCVC system model is basically a hierarchical voltage control approach that operates at three different voltage control levels which consists of Tertiary, Secondary and Primary voltage control modules. The A2 CLCVC based system model will be used to coordinate and optimize the voltage control operation in order to improve security, quality and economic of Malaysian Transmission System. To verify the A2 CLCVC model system performance, two new simulation methodologies based on PSS/E simulation software has been developed: 24-hours Load Flow Python-programming (24LFP-PSS/EM) and 24-hours dynamic simulation based method (24DS-PSS/EM). The two simulation methodologies results has shown that the proposed A2 CLCVC system can provide great benefits to TNB especially for better voltage control and power system operational. The comparative studies with the commercial automatic voltage control system have shown that the performance of A2 CLCVC system is much similar. © 2014 Praise Worthy Prize S.r.l. All rights reserved.